Comparative Studies of Synthesized Copper Oxide Nanoparticles using Aqueous Extract of Leaves - Emmanuel Oyetola; Friday Nwosu; Gboyega Oluwaseun Oyeleke; Ismaila Olawale; Bosede Mofoluwake Adegoke; Usman Afolabi (Nanochemistry Research)
The use of plant extracts as reducing agents in the synthesis of metal and metal oxide nanoparticles has come into prominence due to their procedural simplicity, precursor’s eco-friendliness, and cost effectiveness.  The phytochemicals in plant extracts works as a reductant when mixed with metal salt solution. In this study, we compared the percentage yields of copper oxide (CuO) nanoparticles synthesized using aqueous leaf extracts of Psidium guajava (guava), Terminalia catappa (tropical almond), Cymbopogon citratus (lemon grass), and Tithonia diversifolia (mexican sunflower) at varying volume-ratios with copper sulphate standard solutions. The optimization study of the biosynthesis mixtures revealed that the mixture with the volume-ratio 1:1 of Cu salt : plant extract gave the highest yields in all samples. The nanoparticles were characterized using Fourier-transformed infra-red (FT-IR) to confirm characteristic bands expected of metal oxide particles at the finger print region. The transmission electron microscope (TEM) presented the average sizes within the range of 3.68 and 7.92 nm, while the energy dispersive X-ray Spectroscopy (EDS) confirmed their high purity due to the absence of other elements except carbon. The biosynthesized nanoparticles are highly pure with their small sizes and this makes them suitable for adsorption applications.